Initial Surgical Treatment for Breast Cancer and the Distance Traveled for Care. Issue 8 (August 2021) - Kirkpatrick, Daniel R.; Markov, Nickolay P.; Fox, Justin P.; Tuttle, Rebecca M.
Background: Geography may influence the operative decision-making in breast cancer treatment. This study evaluates the relationship between distance to treating facility and the initial breast cancer surgery selected, identifying the characteristics of women who travel for surgery. Methods: Utilizing Florida state inpatient and ambulatory surgery databases, we identified female breast cancer patients who underwent surgical treatment from January 1 to December 31, 2013. Patients were subgrouped by distance to treatment facility. The primary outcome was the initial surgical treatment choice. Regression models were used to identify factors associated with greater distance to initial treatment. Results: The final sample included 12 786 patients who underwent lumpectomy, mastectomy alone, or mastectomy with reconstruction. Compared to women who traveled < 4.0 miles, women who traveled > 14.0 miles were younger ( P < .001), more often identified as white with private insurance ( P < .001) and were less likely to have three or more medical comorbidities ( P < .001). With increased travel to treatment, the frequency of lumpectomy decreased ( P < .001), while the frequency of mastectomy with reconstruction increased ( P < .001). Increasing age in years (adjusted odds ratio (AOR) = .98 [95% CI = .98-.99]) and identifying as nonwhite with private (AOR = .70 [.61-.80]) or public insurance (AOR = .64 [.56-.73]) was associated with less frequently travelling for initial breast cancer surgery. Discussion: The relationship between the initial surgical treatment for breast cancer and the distance traveled for care highlights a disparity between those who can and cannot travel for treatment.